Similarities in Pronunciation and Meaning of Local Languages and Arabic: Study Contrastive Linguistics of Sundanese Language and Impact on Learning Arabic - Rizal Firdaus; Ana Choerunisa; Amardin Amardin (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - This study aimed to reveal the Sunda language words originally from the Arabic in the Sundanese language dictionary of Raden Satdjadibrata. It because the entry and spread of the Arabic language in Indonesia were in line with the entry and spread of Islam in this country. And the entry of Islam carried some words that were not found by the Indonesians before, and it greatly affected their language. Especially, among the Sundanese who use Sunda’s language and most of them are Muslim. Design/methodology/approach - This study was carried out on the qualitative methods based on the theory of Miles and Huberman, with data reduction, data display, and conclusion drawing/verification. Findings - This study found 92 Sundanese absorption words in the letter M which came from Arabic, and from these words, we can group them into four groups. The first, and it is number 58 Sundanese words that their meaning wasn’t changed from the Arabic meaning. The second, and it's number 8 the words that extended in their meaning. The third, and it's number 13 the words that got narrow in their meaning. And the fourth, and it's number 13 are the words that changed completely their meaning. Originality/value – from a number of vocabularies found, can be used to facilitate learning Arabic for Sundanese people. so that it can help understand effectively and efficiently. Paper type – Concept Paper